Phosphorus Sorption Characteristics of Red Soils from Lampung, West- and Central Java - Syamsul Arifin Siradz (UNIVERSITY OF LAMPUNG, 2009)
Phosphorus Sorption Characteristics of Red Soils from Lampung, West- and Central Java (S.A. Siradz and R.J. Gilkes): Red soil is a common name used to identify any soil showing yellowish to reddish colour, these soils mainly occur in tropical and subtropical regions. The term is frequently used to convey an image of red, infertile, acid soils in the tropics and is associated with tropical and subtropical climates which are characterized by high temperature and humidity. Major soil constraints to crop production may include low pH, low available P and high P fixation capacity, toxicity due to Al and sometimes Mn and Fe, deficiencies of N, Ca, Mg, K, and micronutrients e.g. Mo, Zn and Cu, low CEC and low base saturation, and very low content of weatherable minerals. The aim of this study was to determine the phosphorus sorption characteristics of red soils from Lampung, West Java and Central Java. Soils were sampled at depth of 0-20 cm from minimally disturbed sites after discarding the uppermost few cm consisting of an accumulation of litter. The samples were air-dried, crushed using a ceramic mortar and pestle and then passed through a 0.5 mm stainless steel sieve. Measurements of P sorption were conducted by equilibrating 200 mg of air dry soil (<0.5 mm) in 20 mL 0.2 M KCl containing 0-30 mg PmL-1. P concentrations in filtrate were determined by the molybdate blue method. Phosphorus sorption data for soils were fitted to simple Langmuir and Freundlich isotherm equations and both equations described the data equally well. Langmuir P sorption maximum (xm) for soil ranged from 719-2747 µg Pg-1, with median values of 1.825 µg Pg-1. There were systematic decreases in the values of Langmuir sorption maximum (xm) for soils from Lampung > West Java and Central Java. Values of pH(NaF), Ald, and exchangeable Ca were most predictive of P sorption in these soils.